Analysis of plastic debris on Malaysian beaches / Liyana ‘Izzati Aris - Aris, Liyana ‘Izzati (2012)

(untitled)
Plastic debris is the main cluster of solid waste component present in the marine environment. Anthropogenic activities namely recreational and fishing activities are believed to contribute to the abundance of plastic debris (1 – 30 mm in size) especially along the beach. This study was undertaken to quantify and assess the degree of plastic debris buried in sand according to size with a view to classify such debris deposition at some Malaysian beaches. Another objective, the abundance distribution of the buried plastics was also studied in relation to the tidal zones of the beaches. Six selected beaches (in three different states of Malaysia) served as the representative of the fishing and recreational beaches in this study namely; Teluk Kemang Beach, Pasir Panjang Beach, Batu Burok Beach, Seberang Takir Beach, Tanjung Aru Beach and Teluk Likas Beach. Plastic debris were sampled once a month for three consecutive months. At each beach, triplicates of 12.5 L of sand samples were collected from different tidal zones. The sand samples were sieved to collect and group small plastic debris according to types and sizes. A total of 2,542 pieces of plastics were collected from all selected beaches with a density of 265.30 g/m2. Small-plastic debris occurred on all of the beaches, but the greatest abundance was in Seberang Takir Beach (879 items/m2), followed by Batu Burok Beach (780 items/m2), Teluk Likas Beach (249 items/m2), Teluk Kemang Beach (231 items/m2) and Pasir Panjang Beach (211 items/m2). The least abundance of plastic pieces was collected in Tanjung Aru Beach (192 items/m2). Different types of small plastic particles found in this study were classified into film (36.59%), foam (23.29%), fragment (13.34%), line (25.29%) and pellet (1.49%). The presence of small sized-plastics debris was due to the physical and chemical degradation. Plastic debris buried at different tidal zones have the potential to cause changes to the structure and profile of the sand. The presence of small plastic debris iii could pose adverse impacts to marine ecosystem, especially to marine species. This study documents for the first time presence of small plastic debris on Malaysian beaches. Thus, more studies need to be conducted to enable more understanding on this scenario.